Thyroid Disorders in Patients with Polycystic Ovarian Syndrome in a Tertiary Care Center: An Observational study - Jyotshna Sharma; Bimita Mahat; Sanjeeb Tiwari; Niraj Kumar Singh; Durga Thapa; Ranjana Yadav (Journal of Nepal Medical Association)
Introduction: Polycystic ovarian syndrome is the most common endocrine and metabolic disorder in women of childbearing age, affecting 3–15% of women worldwide, leading to reproductive, metabolic, and psychological issues. Patients with polycystic ovarian syndrome require rigorous thyroid function detection, monitoring, and correction over time. In this study, we aimed to evaluate the clinical presentations and thyroid dysfunction in patients with polycystic ovarian syndrome. Methods: An observational study was done in patients with polycystic ovarian disease presenting to a tertiary care centre over six months, from December 2023 to May 2024 Total population sampling was done. All the women during the study period diagnosed with polycystic ovarian disease based on Rotterdam criteria were included in the study after getting ethical approval from the institutional review board. (Reference number: 20102023/03). Results: The mean age of women in the study was 24.74±5.01 years. A total of 28 (31.46%) patients of polycystic ovarian disease had hyperthyriodism, hypothyroidism was found in 13 (14.60%) and subclinical hypothyroidism was found in 6 (6.74%) patients. All the women had menstrual irregularities. Regarding androgenic characteristics, 53 (59.55%) of patients presented with hirsutism, 43 (48.51%) presented with acne, 13 (14.61%) women had alopecia, and 4 (4.49%) women had acanthosis. Conclusions: Hyperthyroidism, hypothyroidism and subclinical hypothyroidism were prevalent in polycystic ovarian disease patients, emphasizing the need for thorough thyroid evaluation in polycystic ovarian disease patients due to its impact on metabolic and reproductive health. High rates of menstrual irregularities, androgenic symptoms like hirsutism and acne, and fertility challenges were also prevalent, aligning with findings from similar studies.